Amílcar Cabral and the Liberation of Guinea-Bissau and Cape Verde: International, Transnational, and Global Dimensions. Issue 6 (1st November 2020) - Lopes, Rui; Barros, Víctor
Abstract: This themed section explores various international and transnational dimensions of the struggle for the decolonisation of Guinea-Bissau and Cape Verde in the 1960s and early 1970s. Its articles analyse how the path to independence of these relatively small West African nations tied into a wide array of interconnected historical processes taking place around the world, from the streets of Paris to the Great Hall of the People, in Beijing. The aim is to shed new light on the circulation of ideas and foreign connections involved in this struggle, especially those of Amílcar Cabral (1924–73), founding leader of the liberation movement PAIGC and widely regarded as a key thinker of African emancipation, alongside Frantz Fanon and Kwame Nkrumah. In particular, this collection of articles examines how the struggle both shaped and was shaped by larger and/or distant trends, including Third World solidarity networks, the spread of the Cold War to Africa, and the impact of tiers-mondisme in the northern world. It thus contributes to assess the impact of African politics beyond the African continent, as well as to highlight the role of the international community in African liberation and in the emergence of postcolonial states.